MANAJEMEN PENGAWAS PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SIMEULUE - Sudirman, Murniati AR, Bahrun (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: School supervisor is a person who monitors the quality of education provided by schools. This study aims to examine: (1) supervisor’s planning mechanisms, (2) supervisor’s assignment, placement, and career development procedures, (3) supervisor’s monitoring and performance assessment mechanisms, (4) supporting and challenging factors of teachers at the Ministry of Religious Affairs of Simeulue Regency. This study employs descriptive method and qualitative approach. Research data is collected using interviews, observation techniques, and documentation study. Research subjects consist of Head of Ministry of Religious Affairs, Head of Sub Division of Administration, Vice Head for Academic Affairs, Head of Islamic Religious Education, and Supervisor Coordinator of Education Department, Supervisors, and Supervisors candidates. Data is analyzed using reduction, displaying, concluding, and data verification techniques. The results show that (1) mechanisms used in supervision planning or recruitment process for supervisors has not met the selection criteria set out for organizational need, in fact, the recruitment process tends to be subjective, thus discriminative. (2) Supervisors supervisor’s assignment, placement and career development procedures are bureaucratic, subjective, and disorganized. (3) Mechanisms used in monitoring and performance assessment of supervisors are not in line with Standard Operational Procedure, and (4) Supporting factors only limited to positional allowance and certification allowance. Meanwhile, a number of hurdles face by supervisors including lack of attention from the Ministry of Religious Affairs towards the position, welfare, and complaints. In short, it can be concluded that supervisor management at the Ministry of Religious Affairs Office has not been implemented in accordance with existing regulations.Keywords: management, personel, islamic school supervisor Abstrak: Pengawas merupakan personil yang dapat mempengaruhi mutu pendidikan secara berkelanjutan. Penelitian ini bertujuan untuk mengetahui tentang: (1) mekanisme perencanaan pengawas, (2) prosedur pengangkatan, penempatan, dan pengembangan karir pengawas, (3) mekanisme pengawasan dan penilaian kinerja pengawas, dan (4) faktor-faktor pendukung dan penghambat pengawasan guru pada Kantor Kementerian Agama Kabupaten Simeulue. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melalui: observasi, wawancara, dan studi dokumentasi. Subjek penelitian ini adalah: Kepala Kantor Kementerian Agama Kabupaten Simeulue, Kepala Sub Bagian Tata Usaha, Kepala Seksi Pendidikan Madrasah, Kepala Seksi Pendidikan Agama dan Kependidikan Islam, Koordinator Pengawas Dinas Pendidikan, pengawas, dan calon pengawas. Data dianalisis dengan cara mereduksi, mendisplay, menarik kesimpulan, dan verifikasi data. Hasil penelitian menunjukkan: (1) mekanisme perencanaan pengawas belum melalui analisis kebutuhan jabatan sesuai formasi dan kriteria kebutuhan organisasi, rekrutmen dan seleksi bersifat tertutup, transaksional, dan diskriminatif, (2) prosedur pengangkatan, penempatan, dan pengembangan karir pengawas terkesan sangat birokratis, kurang bertanggungjawab, belum memenuhi azas kebutuhan organisasi, dan tidak terkoordinasi dengan baik, (3) mekanisme pengawasan dan penilaian kinerja pengawas belum dilaksanakan sesuai Standar Operasional Prosedur (SOP), dan (4) faktor pendukung hanya tunjangan jabatan dan tunjangan sertifikasi. Sedangkan, penghambat pengawasan guru adalah kurang pedulinya Kantor Kementerian Agama Kabupaten Simeulue terhadap latar belakang jabatan, kesejahteraan, dan keluhan para pengawas. Kesimpulan dari penelitian ini adalah manajemen pengawas pada Kantor Kementerian Agama Kabupaten Simeulue belum berjalan sebagaimana peraturan perundang-undangan yang berlaku saat ini.Kata Kunci: Manajemen, personil, dan pengawas madrasah